Developmental disparities in sedentary time by period of the day among US youth: a cross-sectional study - María Enid Santiago-Rodríguez; Jinsong Chen; Karin A. Pfeiffer; David X. Marquez; Angela Odoms-Young; Eduardo Esteban Bustamante (BMC, 2022)
Abstract Background Definitive evidence shows sedentary time (ST) is an independent risk factor for chronic disease, irrespective of physical activity. Despite calls to limit youth ST, studies demonstrate a spike in ST at the transition from childhood to adolescence. Identifying periods of the day (e.g., before school, during school, afterschool, and evenings) during which ST is higher in adolescents vs. children-that is, specifying when within daily routines ST disparities emerge-may be important to inform intervention strategies, as periods of the day correspond with variations in setting and supervision. The purpose of this study was to examine device-assessed ST engagement by period of day and developmental stage in a nationally representative sample of United States youth. Methods Youth (N = 2,972 between 6-18 years) from the 2003-2004 and 2005-2006 waves of NHANES reported demographic variables and wore an accelerometer for seven consecutive days to determine ST. Linear regression analyses were applied to study associations between ST and developmental stage (childhood or adolescence) by period of the week and weekend days, while controlling for sex, race/ethnicity, annual family income, and body mass index. Results Adjusted linear regressions (p-values < 0.0001) showed that adolescents were more sedentary than children during school, afterschool, and weekday evening periods as well as all the weekend periods. However, during school (36.3 ± 7.3 vs. 28.2 ± 7.2 min/hour; b = -7.4 [-8.1, -6.6]) and afterschool periods (31.1 ± 7.7 vs. 22.7 ± 7.0 min/hour; b = -7.8 [-8.6, -7.0]) showed the largest weekly ST disparities by developmental stage. Overall, the during school and after school hours constitute most (during school = 35% and afterschool = 16%) of the weekly ST disparity between children and adolescents. Conclusions Our data provide interventionists with estimates of the potential for ST reduction in each setting and period of the day among US adolescents. Future research should gather information about the barriers and facilitators of ST in adolescents by period of the day to help understand factors driving disparities.